PENGGUNAAN METODE DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN DAN KOMPETENSI SISWA PADA MATA PELAJARAN BISNIS DIGITAL KELAS XI BD 2 DI SMK NEGERI 1 TASIKMALAYA - Rostini, Neni (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
This research aims to increase student activity and competence in the Digital Business subject class XI BD 2 at SMK Negeri 1 Tasikmalaya through the application of discovery learning methods. This research is Classroom Action Research (PTK) using the Kemmis and Mc Taggart model which was carried out in two research cycles. The subjects of this research were class XI BD 2 students at SMK Negeri 1 Tasikmalaya for the 2022/2023 academic year, totaling 35 students. The data collection technique in this research uses observation for implementing learning and student activity, tests for cognitive competency, and documentation. The success indicator for this research is more than 70% of student activity and 75% of students achieved a KKTP of 76. The research results show that through the application of the Discovery Learning learning method it can increase student activity and competence in Digital Business subjects. This can be seen from: (1) there is an increase in student activity in each cycle. Student activity in cycle I was 40.13%, and cycle II was 76.16%; (2) there is an increase in class averages and student learning completeness. The class average in cycle I was 75.74, and cycle II was 87.33. Student learning completeness as measured by the cognitive competency test in cycle I was 67.74%, and cycle II was 93.33%.